Akkermansia muciniphila and Parabacteroides distasonis as prognostic markers for relapse in ulcerative colitis patients - Mendes-Frias, Ana; Moreira, Marta; Vieira, Maria C.; Gaifem, Joana; Costa, Patrício; Lopes, Luís; Silvestre, Ricardo (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Ulcerative colitis is an inflammatory disorder characterized by chronic inflammation in the gastrointestinal tract, mainly in the colon and rectum. Although the precise etiology of ulcerative colitis remains unclear, recent research has underscored the significant role of the microbiome in its development and progression. Methods The aim of this study was to establish a relationship between the levels of specific gut bacterial species and disease relapse in ulcerative colitis. For this study, we recruited 105 ulcerative colitis patients in remission and collected clinical data, blood, and stool samples. Akkermansia muciniphila and Parabacteroides distasonis levels were quantified in the stool samples of ulcerative colitis patients. Binary logistic regression was applied to collected data to predict disease remission. Results The median time in remission in this cohort was four years. A predictive model incorporating demographic information, clinical data, and the levels of Akkermansia muciniphila and Parabacteroides distasonis was developed to understand remission patterns. Discussion Our findings revealed a negative correlation between the levels of these two microorganisms and the duration of remission. These findings highlight the importance of the gut microbiota in ulcerative colitis for disease prognosis and for personalized treatments based on microbiome interventions.